PENGARUH SIKAP DAN NORMA SUBYEKTIF MASYARAKAT KOTA DENPASAR TERHADAP NIAT BELANJA PADA PASAR TRADISIONAL - Ni Made Rastini (Faculty of Economics and Business Udayana University, 2013)
This research was conducted by taking 100 respondents in the traditional markets of Denpasar traditional market. Data was collected using questionnaires. The variables measured from the sample consist of evaluation of the beliefs, subjective norm and the influence on the intend to shop in traditional markets in Denpasar regency. The results of regression analysis found that the evaluation of beliefs and subjective norms affect consumers’ shopping intentions in a traditional market, in which subjective norms variable are more dominant affecting the spending intentions